EVALUATION OF ACUTE AND SEMI-CHRONIC TOXICITY OF THE REMEDY “BO PHE DINH SUYEN QY” ON EXPERIMENTAL ANIMALS - Nguyen Thanh Ha Tuan; Nguyen Thuong (Tạp chí Y học Quân sự, 2024)
Purpose: To evaluate the acute toxicity and semi-chronic toxicity of the remedy “Bo phe dinh suyen QY” on experimental animals. Subjects and methods: The remedy “Bo phe dinh suyen QY” meeting basic standards was used to evaluate for acute toxicity in Swiss white mice, and for semi-chronic toxicity in Wistar white rats. Acute toxicity was assessed according to the Litchfield-Wilcoxon method. Sub-chronic toxicity was assessed according to the guidance of the Ministry of Health of Vietnam. Results: The remedy “Bo phe dinh suyen QY” at a dose of 375 g/kg mouse body weight/24 hours did not cause acute toxicity or death of experimental mice. For 28 consecutive days, rats administered “Bo phe dinh suyen QY” at doses of 18.2 g/kg/day and 54.6 g/kg/day without affecting their general condition and hematological indices. Conclusions: The remedy “Bo phe dinh suyen QY” was safe in the assessment of acute toxicity (on mice) and semi-chronic toxicity (on rats).